1996
DOI: 10.1006/cyto.1996.0010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines and their receptors by psoriatic fibroblasts I. Altered IL-6 synthesis

Abstract: Interleukin(IL-)6 is overproduced in psoriatic lesions. We investigated the contribution of dermal fibroblasts to the local IL-6 production. Fibroblasts (passageno. 2 to 6) derived from lesional psoriatic (PP) and normal human (NN) skin were used to analyse the secretion of IL-6, and the related cytokines IL-1, IL-8 and TNF-alpha, and the expression of their corresponding mRNA by bioassay, ELISA and Northern hybridization, respectively. PP fibroblasts cultured under serum-free conditions produced increased amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…IL-6 and IL-8 were also elevated in the patient's serum (Supplemental Table 3). Elevation of IL-6 and IL-8 has been demonstrated in psoriatic skin and fibroblasts and is considered an amplifier of skin inflammation (21). The classical proinflammatory cytokine TNF-α was normal in the patient, consistent with the failure of the dermatitis to respond to treatment with TNF-α inhibitor etanercept.…”
Section: Figurementioning
confidence: 61%
“…IL-6 and IL-8 were also elevated in the patient's serum (Supplemental Table 3). Elevation of IL-6 and IL-8 has been demonstrated in psoriatic skin and fibroblasts and is considered an amplifier of skin inflammation (21). The classical proinflammatory cytokine TNF-α was normal in the patient, consistent with the failure of the dermatitis to respond to treatment with TNF-α inhibitor etanercept.…”
Section: Figurementioning
confidence: 61%
“…There were, however, prominent HLA-DR findings in tbe dermis, presumably identifying dermal macrophages and dendritic cells (32) and supporting the conclusion that the source of the cytokines in the microdialysates was predominately dermal. Which cells within the dermis are actually producing the cytokines in this study is as yet unclear, but several types of tissue cells are known to produce and store pro-inflammatory cytokines (33)(34)(35). The combination of microdialysis with end-point tissue biopsy gives complementary information in the experimental setting and is likely to be of further use in studies of diseased skin in which the number of cells in the dermis is greater.…”
Section: Discussionmentioning
confidence: 96%
“…IL-6 is produced by numerous cell types, including macrophages, monocytes, fibroblasts, endothelial cells, and smooth muscle cells. In vivo studies have shown low levels of constitutive IL-6 production by fibroblasts of different origins, including dermal (5), liver (myo) (24), duodenal (22), renal (15), foreskin (14), human periodontal ligament (20,27), oral fibrotic submucosal and buccal mucosal (3), and normal human gingival (3,11,12,19) origins.…”
mentioning
confidence: 99%